Fabrication and Magnetic Properties of Sintered SrFe\(_{12}\)O\(_{19}\)-NiFe\(_{2}\)O\(_{4}\) Nanocomposites - Nga, Tran Thi Viet; Loan, To Thanh (Communications in Physics, 2017)
Two series of SrFe\(_{12}\)O\(_{19}\)/NiFe\(_{2}\)O\(_{4}\) nanocomposite ferrites sintered in air at 850\rc{}C and 950\rc{}C were prepared using SrFe$_{12}$O$_{19}$ and NiFe\(_{2}\)O\(_{4}\) nanopowders obtained via sol-gel method. The phase composition, surface morphology and magnetic properties of the composites were investigated using XRD, SEM and VSM respectively. For the SrFe$_{12}$O$_{19}$/NiFe$_{2}$O$_{4}$ ferrites with volume ratio ranging from 61 to 21 and sintered in 850\(\r{}\)C for 5 hours in air, all the specimens are composed of two phases but exhibit a typical single-phase magnetic behavior, indicating the existence of exchange coupling (EC) between the magnetically hard and soft phases. The value of coercivity H\(_{c}\) decreases from 6.19 kOe to 0.574 kOe when volume of SrFe$_{12}$O$_{19}$ decreases from 6 to 1. While the samples with a mass ratio of \(R_{m}\)= SrFe\(_{12}\)O\(_{19}\)/ NiFe\(_{2}\)O\(_{4}\) varying from 31 to 13 sintered in 950\rc{}C for 5 hours characterized with a ``bee waist'' type hysteresis loop. These results reveal that the magnetically hard and soft magnetic phases are not exchange- coupled. The saturation magnetization (\(M_{S}\)) increases from 36 emu/g to 43.3 emu/g when \(R_{m}\) decreases from 31 to 13 and then decreases with \(R_{m}= 12\) and 13.